Are there subtle, genome-wide epigenetic alterations in normal offspring conceived from Assisted Reproductive Technologies? - Batcheller, April (2011)
OBJECTIVE: To review recent data regarding subtle, but widespread epigenetic alterations in phenotypically normal offspring conceived of ART compared to offspring conceived in vivo. DESIGN: A PubMed computer search was performed to identify relevant articles. SETTING: Research institution. INTERVENTION(S): None. RESULT(S): Studies in animals indicate that in vitro culture may be associated with widespread alterations in imprinted genes, compared to in vivo-conceived offspring. Recently, studies in humans have likewise demonstrated widespread changes in DNA methylation, including genes linked to adipocyte development, insulin signaling, and obesity in offspring conceived by ART, compared to in vivo-conceived children. Changes in multiple imprinted genes following ART were also noted in additional studies, which suggested that the diagnosis of infertility may explain the differences between in vivo-conceived and ART offspring. CONCLUSION(S): These data suggest that ART is associated with widespread epigenetic modifications in phenotypically normal children, and that these modifications may increase risk of adverse cardiometabolic outcomes. Further research is needed to elucidate the possible relationship between ART, genome-wide alterations in imprinted genes, and their potential relevance to subtle cardiometabolic consequences reported in ART offspring.